Small-cell neuroendocrine carcinoma of the esophagus: an autopsy case report - Mariana Bellaguarda de Castro Sepulvida; Augusto Vieira Amaral; Pompeu Tomé Ribeiro de Campos; Carlos Osvaldo Teixeira; Maria Aparecida Barone Teixeira (University of São Paulo, 2014)
Small-cell neuroendocrine carcinoma is a well-known aggressive neoplasia, which is usually associated with a poor prognosis. The lung is the most common primary site, but other organs may be involved, especially those of the digestive tract. The authors report the case of a 71-year-old Caucasian, male patient who was admitted because of congestive heart failure and loss of vision accompanied by right proptosis. Skull and sinuses computed tomography showed a tumoral mass involving the posterior region of the right eye, local bones, and paranasal sinuses. Because of severe hemodynamic instability, the patient died and no diagnostic investigation could be performed. Autopsy findings revealed small-cell neuroendocrine carcinoma of the esophagus and metastases to the posterior region of the right ocular globe, which affected the sinuses, the muscles of the ocular region, the orbit bones, the skull, the meninges and the brain, plus the liver, adrenal glands, and the pericardium. This case called the author's attention to the extent of the metastatic disease in a patient who was firstly interpreted as presenting solely with congestive heart failure. The autopsy findings substantially aid the understanding of the immediate cause of death.